Delivering Functional Imaging on the MRI-Linac: Current Challenges and Potential Solutions. Issue 11 (November 2018) - Datta, A.; Aznar, M.C.; Dubec, M.; Parker, G.J.M.; O'Connor, J.P.B.
Abstract: Magnetic resonance imaging (MRI) is a highly versatile imaging modality that can be used to measure features of the tumour microenvironment including cell death, proliferation, metabolism, angiogenesis, and hypoxia. Mapping and quantifying these pathophysiological features has the potential to alter the use of adaptive radiotherapy planning. Although these methods are available for use on diagnostic machines, several challenges exist for implementing these functional MRI methods on the MRI-linear accelerators (linacs). This review considers these challenges and potential solutions.